Initiation of nuclear disassembly during apoptosis - Carson, Christine (University of Ottawa (Canada), 2003)
Apoptosis has long been recognised by two hallmarks of the end stage of nuclear breakdown: collapse of the chromatin and oligonucleosomal cleavage of the DNA. Control of initial nuclear events, such as high molecular weight (HMW) DNA and specific nuclear matrix cleavage, and their relationship to the cytoplasmic steps of cell death has not been elucidated. Examination of the relationship between events in the cell death path is limited by the stochastic nature of the process in all known models, which forces investigators to deal with mixed populations, combined with the tight temporal relationship of events in single cells. To determine whether a mitochondria-based signal could be responsible for the initial nuclear events of apoptosis, the timecourse of cell death in both primary rat thymocytes treated with dexamethasone or VM-26 (teniposide) and human Jurkat T cells treated with anti-Fas was first established using several cytoplasmic and nuclear criteria of cell death. Initial nuclear events were characterised at the single cell level at early time points in the apoptotic response by staining of the chromatin, immunofluorescence labelling of nuclear matrix and in situ detection of DNA breaks by TUNEL. Reorganisation of the matrix attachment region (MAR)-binding protein SATB1 was uniquely detected prior to chromatin collapse but after the appearance of initial DNA breaks. Early reorganisation of a portion of SATB1 was followed by increasing DNA cleavage, the reorganisation of the internal nuclear matrix, represented by NuMA, coincident with chromatin collapse and maximal DNA breaks. Peripheral nuclear proteins, represented by lamin B, lamin B receptor (LBR) and PI2, were not affected until after chromatin collapse, if at all. SATB1 reorganisation and initial DNA breaks were then compared with mitochondrial function detected in live Jurkat cells by uptake of DiOC6(3), using flow cytometry and cell sorting to isolate those cells with normal mitochondrial membrane potential, normal size and intact plasma membrane from the mixed population of anti-Fas treated Jurkats. At the single cell level, changes in nuclear morphology, initial DNA cleavage and early reorganisation of SATB1 were detected in a minority of the "apparently normal" cells that displayed a normal mitochondrial membrane potential. Specific cleavage of SATB1 in these cells was detected by Western blotting and accumulation of single strand breaks demonstrated as well, using two-dimensional electrophoresis of DNA. (Abstract shortened by UMI.)
Keywords: Biology, Cell.